Growth Curve Patterns in Broilers and KU-Phuphan and Pradu Hang Dam Chickens Using Nonlinear Models - Plaengkaw, S.; Khumpeerawat, P.; Sukprasert, C.; Phongphanich, P.; Saowaphak, P.; Lokaewmanee, K. (Tropical Animal Science Journal, 2026)
The growth performance of poultry is an important economic indicator and is crucial for the accurate modeling of growth curves, particularly for indigenous chicken breeds. Therefore, the optimal nonlinear growth model was investigated for commercial broilers and for two indigenous chicken breeds (KU-Phuphan and Pradu Hang Dam), breed-specific characteristics were delineated, and the influence was examined of sex on growth patterns. Chickens were weighed every 2 weeks. The broilers were followed for 6 weeks (fast-growing chickens) and the indigenous chickens (KU-Phuphan and Pradu Hang Dam) for 12 weeks (slow-growing chickens), with all groups analyzed for growth pattern using five nonlinear models. All models were evaluated for performance using R², RMSE, MAE, AIC, and BIC. The Gompertz model provided a better fit for the broilers, while the Hossfeld model was best for both indigenous breeds, with the models providing very good levels of prediction. The best-fitting models showed that growth parameters were different between breeds and between sexes. For example, in the indigenous breeds, the males had higher maximum body weight, cumulative weight gain, and growth rate than the females. However, there were no consistent sex differences in the broilers during their 6-week production period. There were only significant impacts of breed × sex interaction at ages 2 and 4 weeks. Overall, the optimal models for predicting chicken growth were specific to each breed. This finding should be useful for making decisions about breeding, feeding, and managing native poultry production systems.